Shared genetic factors influence risk for bipolar disorder and alcohol use disorders - Peralta Fernández, Juan Manuel (2014)
Bipolar disorder and alcoholism have high rate comorbidity, with more than 50% of alcoholism occurrence in bipolar disorder. While there is evidence that both disorders are heritable, it is unclear if the same genetic factors predispose them. The aim of this study is to determine if common genetic factors influence risk for bipolar disorder and alcoholism. A total of 733 Costa Rican individuals from 61 extended pedigrees, selected for sibling pairs with a diagnosis of bipolar disorder, participated in the study. All subjects completed a diagnostic interview, the Barratt Impulsiveness Scale (BIS-11) and Fagerström questionnaire for Nicotine Dependence. Heritability and bivariate correlations were estimated using SOLAR. Based on a best-estimate process, twenty-nine percent of the sample met criteria for broad bipolar phenotype, 23% bipolar I disorder, 15% alcoholism, 32% smoking, only 2% drug abuse, and 20% for an anxiety disorder. Thirty-three present did not meet criteria for a lifetime diagnosis. In the broad bipolar phenotype group, 28% had a lifetime diagnosis of alcoholism. The heritability estimated for broad bipolar phenotype was h2=0.559 (p=7.0x10-6) and for alcoholism was h2=0.752 (p=3.0x10-7). Only alcoholism (ρg=0.600, p=0.002) and habitual smoking (ρg=0.717, p=2.1x10-4) were significantly genetically correlated with the broad bipolar phenotype. A similar pattern of results was observed for the bipolar I disorder phenotype. The current findings strongly imply that shared genetic factors increase risk for bipolar disorder and addictive disorders. A better understanding of this comorbidity could improve clinical outcomes and potentially facilitate novel treatments.